A methodology for tracing the rank invariance region in multi-criterion selection problems: Application to negative emission technologies - Tan, Raymond Girard R. (Animo Repository, 2019)
It has been previously established that, for multi-criterion selection problems, over a finite set of options, solved via simple additive weighting, there exists a set of weights for which the optimal alternative remains the best choice. This invariance region in the n-dimensional hyperspace defined by the problem criteria contains the set of all weights for which the optimal solution is robust to preference changes. When the set of options is a continuum, there are no known invariance regions reported in the literature. In this work, we develop a procedure to characterize and trace this invariance region when the number of options is finite. The methodology is demonstrated on a case study involving a selection of negative emission technologies based on carbon sequestration potential, water footprint, energy demand, and cost. © 2019, Springer Nature Singapore Pte Ltd.